KEBIJAKAN PENANGANAN STUNTING OLEH PEMERINTAH KOTA PALU SEBAGAI UPAYA MEWUJUDUKAN SUSTAINABLE DEVELOPMENT GOALS - srifridayanti (Universitas Bina Taruna Gorontalo, 2025)
This research aims to find out the policy of handling stunting by the Palu City Government in realizing the Sustainable Development Goals (SDGs) and to find out what factors hinder the Palu City government in handling stunting. The method used in this research is a qualitative approach and is descriptive, qualitative research is a research method used to research on natural object conditions, as opposed to experiments, where the researcher is the key instrument. Qualitative research aims to obtain a complete picture of a matter according to the human views studied. Qualitative research deals with ideas, perceptions, opinions or beliefs of the people studied and all of them cannot be measured by numbers. The results showed that the Palu City Government to carry out stunting handling activities in realizing the Sustainable Development Goals (SDGs) divided into 2 actions, namely prevention and control. Preventive actions taken by the Palu City Government are providing education to pregnant women and toddlers regarding the importance of fulfilling nutrition, as well as providing blood or hemoglobin supplements to pregnant women. Population control is also one of the preventive measures taken by the Palu City Government in handling stunting. While in countermeasures, in addition to providing additional food, the government of Palu City conducted training for pregnant women and toddlers.